2022
DOI: 10.1002/cssc.202102750
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled Ketoreductase‐Diaphorase Assay for the Detection of Polyethylene Terephthalate‐Hydrolyzing Activity

Abstract: In the last two decades, several PET‐degrading enzymes from already known microorganisms or metagenomic sources have been discovered to face the growing environmental concern of polyethylene terephthalate (PET) accumulation. However, there is a limited number of high‐throughput screening protocols for PET‐hydrolyzing activity that avoid the use of surrogate substrates. Herein, a microplate fluorescence screening assay was described. It was based on the coupled activity of ketoreductases (KREDs) and diaphorase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[58] Consequently, many companies have invested in commercial panels of KREDs from known or metagenomic sources along with assays to screen large libraries at once. [59] Newgas et al isolated a panel of KREDs from an in silico oral microbiome metagenomic library, which demonstrated excellent activity on a number of sterically hindered ketones. [60] It has also been shown that metagenomic KREDs can be used to make synthetically challenging drug fragments.…”
Section: C=x Bond Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] Consequently, many companies have invested in commercial panels of KREDs from known or metagenomic sources along with assays to screen large libraries at once. [59] Newgas et al isolated a panel of KREDs from an in silico oral microbiome metagenomic library, which demonstrated excellent activity on a number of sterically hindered ketones. [60] It has also been shown that metagenomic KREDs can be used to make synthetically challenging drug fragments.…”
Section: C=x Bond Reductionmentioning
confidence: 99%
“…Ketoreductases (KREDs) or alcohol dehydrogenases (ADHs) are able to the reduction of ketones in a wide range of different molecules [58] . Consequently, many companies have invested in commercial panels of KREDs from known or metagenomic sources along with assays to screen large libraries at once [59] . Newgas et al.…”
Section: Metagenomics and Its Role In Biotechnologymentioning
confidence: 99%
“…Leakage is a well-documented challenge in microfluidic assay development, preventing the use of the commonly large and aromatic probes for all but the fastest reactions [48][49][50][51][52] . This poses a hitherto unsolved challenge for fluorogenic NAD(P)H quantification as resorufin, the sole published fluorogenic probe for NAD(P)H detection [49,53] , is hydrophobic and consequently only compatible with very short reaction times in microfluidic droplets [54] . Previous work has shown that adding charged groups to fluorophores [52] and specifically coumarins [12,55] mitigates droplet leakage and improves aqueous solubility.…”
Section: Sensing Nanomolar Concentrations Of Nadh Via Glutathione-med...mentioning
confidence: 99%
“…For instance, bulk UV absorbance measurement of the reaction supernatant has been proposed as a simpler method, but it comes with some disadvantages: depending on the mode of action of the enzyme (if it produces monomers or oligomers), the measurements can be inaccurate and difficult to compare . Alternatively, the utilization of ketoreductases (KREDs) for the detection of released ethylene glycol (EG) showed a good correlation to the HPLC results . Another approach for quantifying PET degradation products, initially introduced by Ebersbach et al, converts products into fluorescent compounds through a mechanism driven by the iron autoxidation-mediated generation of free hydroxyl radicals .…”
Section: Introductionmentioning
confidence: 99%
“… 14 Alternatively, the utilization of ketoreductases (KREDs) for the detection of released ethylene glycol (EG) showed a good correlation to the HPLC results. 15 Another approach for quantifying PET degradation products, initially introduced by Ebersbach et al, converts products into fluorescent compounds through a mechanism driven by the iron autoxidation-mediated generation of free hydroxyl radicals. 16 However, Zurier and Goddard highlighted that this particular protocol encounters limitations that arise from the fact that the mono-(2-hydroxyethyl) terephthalate (MHET) exhibits a lower fluorescent extinction coefficient compared to that of terephthalic acid (TPA), 13 so in a hydrolysis mixture where both products are present, TPA will contribute mostly to fluorescence.…”
Section: Introductionmentioning
confidence: 99%